Self-depuration capacity in a lotic environment based on the mathematical model of Streeter-Phelps in northeastern Para (Research, Society and Development, 2021)
The city of Capanema - PA, developed along the banks of the Ouricuri River. In view of this, it is important to know the capacity of self-depuration of this water resource. The objective of this research was to analyze quantitatively and qualitatively the simulation of the self-depuration capacity of this lotic environment, and to propose two mitigating measures for the reduction of the impacts generated in the hydric body and improvements in the quality of the water. The method was deductive, quantiqualitative in scope and applied in nature. The data obtained and analyzed, for the three points, P1, P2 and P3, in the rainy period: for Rio Ouricuri were, DO: x ̅ = 0.26 mg/L; BOD5: x ̅ = 10 mg/L; flow: x ̅ = 1.80 m³/s; temperature: x ̅ = 26 ºC, for the effluent ring: OD: x ̅ = 0.16 mg/L, BOD5: x ̅ = 300 mg/L; flow: 0.88 m³/s; temperature: x ̅ = 26 ºC. In the dry period, for Ouricuri River: OD: x ̅ = 0.16 mg/L; BOD5: x ̅ = 10 mg/L; flow rate: x ̅ = 0.93 mg/L; and temperature: x ̅ = 25 ºC; for the effluent washer: OD: x ̅ = 0.43 mg/L, BOD5: x ̅ = 300 mg/L, flow rate: x ̅ = 0.88 m³/s, and temperature: x ̅ = 27 °C. The values of DO, and BOD are compared with the CONAMA Resolution 357/05, and it was found that they are in non-compliance, therefore, the river is considered polluted for both potability and bathing. Therefore, it is necessary that the responsible bodies in the municipality use the data contained herein to develop mitigation measures for the recovery of the river.